Manajemen Kurikulum dalam Perspektif Beauchamp: Acuan Pengembangan Jurusan di Sekolah Menengah Kejuruan - Fifin Priandono (Journal of Islamic Education Policy, 2018)
ABSRACT., Management is part of a science and art which contains activities in planning, organizing, implementing, and controlling in completing all matters by utilizing all available resources through other people in order to achieve the goals previously set. The curriculum is something that has been planned in the context of children's learning. In the view and traditional thinking of the curriculum, the curriculum is formulated as a number of subjects that must be passed by students in the framework and purpose of obtaining a diploma. can be explained that the management of educational curriculum is a systematic effort by someone through the activities of planning, organizing, implementing and evaluating the curriculum aims to enable students to achieve learning objectives effectively and efficiently. The aim of national education is the goal to be achieved nationally, which is based on the philosophy of a country. The nature of this goal is ideal, comprehensive, intact and becomes the parent of the objectives that are under it.Keyword: Management, Curriculum, Education ABSTRAK., Manajemen adalah bagian dari sains dan seni yang berisi kegiatan dalam perencanaan, pengorganisasian, penerapan, dan pengendalian dalam menyelesaikan semua hal dengan memanfaatkan semua sumber daya yang tersedia melalui orang lain untuk mencapai tujuan yang telah ditetapkan sebelumnya. Kurikulum adalah sesuatu yang telah direncanakan dalam konteks pembelajaran anak-anak. Dalam pandangan dan pemikiran tradisional tentang kurikulum, kurikulum dirumuskan sebagai sejumlah mata pelajaran yang harus dilewati oleh siswa dalam kerangka dan tujuan memperoleh diploma. dapat dijelaskan bahwa manajemen kurikulum pendidikan merupakan upaya sistematis oleh seseorang melalui kegiatan perencanaan, pengorganisasian, pelaksanaan dan evaluasi kurikulum yang bertujuan untuk memungkinkan siswa mencapai tujuan pembelajaran secara efektif dan efisien. Tujuan pendidikan nasional adalah tujuan yang ingin dicapai secara nasional, yang didasarkan pada filosofi suatu negara. Sifat dari tujuan ini adalah ideal, komprehensif, utuh dan menjadi induk dari tujuan yang ada di bawahnya.Kata kunci: Manajemen, Kurikulum, Pendidikan